IMPLEMENTASI PROGRAM PEMBINAAN KOMPETENSI PROFESIONAL GURU DI SMK DARUNNAJAH CIPINING - Syahid Nur Arifin; Mustafa Zahir; Taufik Nur Azis; Ahmad Farid (CV. ALIM'SPUBLISHING, 2023)
Teacher professional competence is very important because it is something that every teacher must have to make quality and carry out the duties of an educator properly. One way to make the competence of a teacher or an educator is by coaching. The development of this competency is very important and needs to be done for a teacher or an educator to make it more effective and efficient in the application of teaching. Descriptive qualitative research method is the method used in this study. Data collection techniques are carried out through observation, interviews, and documentation. From the results of the study, it was found that the implementation of the teacher professional competence development program at Darunnajah Cipining Vocational School was quite good including: MGMP, Taftisy I'dad, Kamisan, Ta'hil, In House Training and Khutbatul 'Arsy, Teacher Supervision (Supervision) and Appreciation (Motivation). From the results of this study, the authors recommend that Darunnajah Cipining Vocational School educational institutions should further improve teacher professional competency development. Keywords: Implementation, Coaching, Competence